2004
DOI: 10.1093/sleep/27.3.459
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Airflow Dynamics During Sleep in Women with Fibromyalgia

Abstract: Inspiratory airflow limitation is a common inspiratory airflow pattern during sleep in women with fibromyalgia. Our findings are compatible with the hypothesis that inspiratory flow limitation during sleep plays a role in the development of the functional somatic syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 28 publications
2
34
0
2
Order By: Relevance
“…In our study, we found OSAS frequency in female patients to be 10.5%. Although our study yielded similar results to those of Moldofsky et al, 33 the difference could be attributed to the fact that the patients in our study were younger, had lower BMI, and were only females.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, we found OSAS frequency in female patients to be 10.5%. Although our study yielded similar results to those of Moldofsky et al, 33 the difference could be attributed to the fact that the patients in our study were younger, had lower BMI, and were only females.…”
Section: Discussionsupporting
confidence: 83%
“…In their study, May et al 32 found OSAS frequency in female patients with FMS as insignificant, while they found this frequency as significant in male patients with FMS, which led them to conclude that further research must be performed on male patients in terms of OSAS risk. Moldofsky et al 33 found moderate to severe obstructive sleep apnea disorder frequency to be 15.3%. In our study, we found OSAS frequency in female patients to be 10.5%.…”
Section: Discussionmentioning
confidence: 98%
“…The similarity of these findings in women with TMD to PSG evaluations of women with fibromyalgia showing increased sleep disruption and inspiratory flow limitation without elevated AHI underscores pain-related arousability as a possible cause of elevated RERA index in TMD. 31,32 It has been suggested that a lower arousal threshold in response to respiratory stimuli may contribute to the etiology of sleep disordered breathing, 33 and elevating the arousal threshold with a hypnotic may reduce the frequency of respiratory events. 34 Therefore, the role of chronic pain conditions in lowering the arousal threshold to respiratory stimuli during sleep needs to be determined in future studies.…”
Section: Pain and Covariate Predictorsmentioning
confidence: 99%
“…(17) Still others, in 2004, found SDB in 27 of 28 women with FMS. (18) However, in various other studies involving larger study samples, no association between FMS and SDB has been observed. (25)(26)(27)(28) Our finding that alpha activity increased during delta sleep in 5 of the 11 cases of FMS is consistent with that of other authors, who observed alphadelta sleep in 20 out of 40 women with FMS.…”
Section: Discussionmentioning
confidence: 90%
“…(17) Another reported fourteen cases of FMS symptom improvement in patients with SDB after three weeks of continuous positive airway pressure. (18) These findings suggest that SDB plays a role in the development of FMS.…”
Section: Introductionmentioning
confidence: 85%